Hydrogel electrode preparation method for freeze-induced ion directional diffusion and electrode system
By using a hydrogel electrode method that induces directed ion diffusion in CO2 mineralized battery system, an orientated micropore structure and ion channel are constructed, which solves the problems of electrode fluid leakage and water surge, and improves the electrode performance and stability , realizes efficient operation of the gas diffusion electrode.
Patent Information
- Application Number
- CN202411282580.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-13
AI Technical Summary
In CO2 mineralized battery system, the pressure drop and capillary phenomenon caused by the flow of the electrode liquid, causing the liquid phase in the microporous layer to occupy the gas channel, making the reaction gas difficult to reach the catalyst, resulting in a decrease in electrolytic performance, and the electrode is prone to appear. The phenomenon of water surge affects system stability.
Using the hydrogel electrode preparation method that induces directed diffusion of ions, the polymer precursor solution is precoated on the catalytic layer and cured under the freezing temperature gradient to form an oriented micron-scale pore structure, and the ions are constructed using the salting effect. The channel realizes the transformation of free water to bound water, avoids leakage of electrode fluid, and a hydrogel layer is installed in the electrode system to block the flow of the two phases.
It effectively solves the problem of water flooding of gas diffusion electrodes, improves ion transport efficiency, enhances the performance of electrode system, extends the service life of electrodes, and improves the mass transfer performance of gas diffusion electrodes, avoids water surges, and improves the system long-term running stability.
Smart Images

Figure CN119133476A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrochemistry, and more specifically, to a method for preparing a hydrogel electrode for cryo-induced ion directional diffusion and an electrode system. Background Art
[0002] In the field of electrochemistry, we have found the following technical problems:
[0003] Gas diffusion electrodes are generally composed of a gas diffusion layer and a catalyst layer. They are an electrode system with porosity, certain water resistance, good conductivity, high active surface area and high catalytic activity. Under working conditions, the gas and electrolyte are in equilibrium in the micropores of the gas diffusion electrode, forming a stable gas-liquid-solid three-phase interface, and electrochemical reactions occur under certain potential conditions. However, in the CO2 mineralization battery system, due to the two-phase flow on both sides of the electrode (the gas diffusion layer side is directly in contact with the reaction gas, and the catalyst layer side is directly in contact with the electrode liquid). The flow of the electrode liquid on the electrode surface will produce a pressure drop on the electrode surface, which is related to factors such as the fluid flow mode and flow rate, and fluid properties. Among them, the capillary phenomenon in the electrode microporous layer will increase the volume fraction of the liquid phase in the microporous layer, so that the gas channels in the original microporous layer are occupied by the liquid phase, and it is difficult for the reaction gas to reach the catalyst surface, resulting in a decrease in electrolysis performance.
[0004] When a through-type water channel network is formed inside the electrode, the electrolyte will leak to the gas side. From a macroscopic perspective, the gas diffusion electrode system leaks and a "water surge" phenomenon occurs. The "water surge" of the electrode will not only reduce the electrochemical performance of the entire battery system, but will also bring a variety of salt ions in the electrolyte into the electrode microporous layer, causing damage to the channels in the electrode microporous layer. In addition, the "interconnection" of fluids in the gas-liquid two-phase flow zone greatly increases the difficulty of device design and greatly reduces the stability of the battery system during long-term operation.
[0005] The formation of the "water surge" phenomenon is mainly due to the existence of mixed and interwoven hydrophilic-hydrophobic channels in the microporous layer and the catalytic layer in the gas diffusion layer. For the hydrophilic channels, there is water seepage; while for the hydrophobic channels, under the impetus of external pressure, water will preferentially enter the larger hydrophobic pores to form a water network. In the battery, the flow of the electrode liquid phase brings about a pressure drop on the electrode surface, and the resistance generated in the local space within the device causes the electrode liquid to generate horizontal pressure. This accelerates the water surge process of the electrode system.
[0006] In order to increase the drainage performance of gas diffusion, the gas diffusion layer is generally treated by adding hydrophobic PTFE to improve the water resistance of the electrode gas diffusion layer, so that the surface and pores of the gas diffusion layer will not be blocked by liquid water. However, due to the poor conductivity of PTFE, and the addition of excessive PTFE will reduce the porosity of the gas diffusion layer, resulting in a decrease in mass transfer performance and a decrease in the electrochemical performance of the electrode. And with the use of the electrode system, the water resistance of the gas diffusion electrode is also constantly decaying. Taking the fuel cell electrode system with a three-phase reaction as an example, with long-term use, the hydrophilicity of the gas diffusion layer surface becomes stronger and stronger, and the concentration polarization in the fuel cell operation increases significantly. This is due to the aging of the electrode, the PTFE coating falls off, the accumulation of hydrophilic impurities, and the change in the porosity distribution of the gas diffusion layer. In fact, people have conducted a lot of improvement research around the problem of water management of gas diffusion electrodes. For example, adding a microporous hydrophobic layer on the basis of a single gas diffusion layer, constructing a double-layer gas diffusion layer, etc. However, the base layer of the double-layer structure is still flooded, and the electrode life and performance are also limited. In addition, there will be pore boundaries at the junction of multiple layers. When running at high current, the mass transfer driving force is large, and water vapor is easily accumulated at the junction, affecting the mass transfer of the gas diffusion electrode. Summary of the invention
[0007] The purpose of the present invention is to overcome the deficiencies of the prior art, and to provide a method for preparing a hydrogel electrode for freezing-induced directional diffusion of ions and an electrode system, which can solve the liquid leakage phenomenon that occurs after long-term use of the gas-liquid-solid three-phase reaction gas diffusion electrode, realize directional ion transport, and improve the efficiency of electrode gas transport, and is particularly suitable for various electrochemical systems with gas-liquid-solid three-phase reactions. In addition, the hydrogel electrode of the present invention can also achieve multi-directional regulation of the performance of the gel layer by matching freezing gradient induction in different directions and selecting different salting-out liquid systems, avoiding the problem of electrode "flooding" caused by long-term contact between the electrode liquid and the gas diffusion electrode catalyst layer, resulting in a decrease in system efficiency, and improving the service life of the electrode. In addition, the presence of the hydrogel layer between the electrolyte and the solid catalyst layer can realize the transformation of interfacial free water to bound water, avoid "water surge", and rely on the directional ion channel constructed inside the hydrogel layer to enhance the transport efficiency of ions and improve the performance of the electrode system.
[0008] The object of the present invention is achieved through the following solutions:
[0009] A method for preparing a hydrogel electrode for cryo-induced ion directional diffusion comprises the following steps:
[0010] Step 1, pre-coating a layer of polymer precursor solution uniformly on the catalyst layer, setting a freezing temperature gradient induction to controllably solidify the polymer solution, during which the polymer chains are squeezed by ice crystal growth to form an oriented micron-scale pore structure;
[0011] Step 2, immersing the electrode after the hydrogel layer is solidified in a salt solution to assist thawing. Under the influence of the hydrophilic group, the surface tension between the polymer chain and the water molecules changes. At this time, there are multiple interactions between the lyophilic ions, polymer chains and water in the system. These interactions are used to fix and enhance the polymer chain structure in the hydrogel. The polymer solution undergoes a liquid-solid-gel three-phase change, free water is converted into bound water, and directional freezing induction and salting-out effects construct ion transport channels inside the gel.
[0012] Furthermore, the freezing temperature gradient induction is set to controllably solidify the polymer solution, and during the solidification process, the polymer chains are squeezed by the growth of ice crystals to form an oriented micron-scale pore structure, which specifically includes the following sub-steps:
[0013] Construct an oriented structure parallel to the diffusion direction in the gel layer: select the direction perpendicular to the plane of the square gel layer as the direction of the freezing temperature gradient. Under the action of this temperature gradient, the water inside the precursor solution grows into ice crystals along this direction. Taking the ion diffusion direction as a reference, the structure finally formed in the gel layer is an oriented porous structure parallel to the diffusion direction.
[0014] Furthermore, the freezing temperature gradient induction is set to controllably solidify the polymer solution, and during the solidification process, the polymer chains are squeezed by the growth of ice crystals to form an oriented micron-scale pore structure, which specifically includes the following sub-steps:
[0015] Construct an oriented structure perpendicular to the diffusion direction in the gel layer: select the direction parallel to the plane of the square gel layer as the direction of the freezing temperature gradient. Under the action of this temperature gradient, the water inside the precursor solution grows into ice crystals along this direction. Taking the ion diffusion direction as a reference, the structure finally formed in the gel layer is an oriented fibrous structure perpendicular to the diffusion direction.
[0016] Furthermore, the precursor solution includes any one of polyvinyl alcohol (PVA) solution, chitosan, sodium alginate, and gelatin.
[0017] Furthermore, the setting of freezing temperature gradient induction includes any one of uniform random freezing, parallel orientation freezing, and vertical orientation freezing.
[0018] Furthermore, the cations in the salt solution include Na + , K + NH4 + , Ca 2+ Any one of; anion citrate, SCN in the salt solution - 、ClO4 - ,I - 、NO3 - Br- Any of the ions.
[0019] A hydrogel electrode system for cryo-induced ion directional diffusion, comprising:
[0020] Gas diffusion layer, catalyst layer and hydrogel layer;
[0021] The gas diffusion layer is in direct contact with the reaction gas, and the gas diffuses into the electrode system through the macroporous base layer and the microporous layer under the action of the concentration gradient; the hydrogel layer is a semi-solid gel and is in direct contact with the electrode liquid. The free water in the electrolyte cannot freely diffuse out of the electrode system through the hydrogel layer under pressure and concentration gradient. There are ion channels inside the hydrogel layer, and the ions in the electrode liquid are transported to the catalytic layer for reaction, thereby utilizing the hydrogel layer to realize the conversion of free water into bound water; the catalytic layer adsorbs the reaction gas diffused from the gas diffusion layer and the ions transported by the hydrogel layer, and is in direct contact with the electrode liquid; the catalytic layer is attached with a catalyst, which provides reaction sites for the gas adsorbed by the gas diffusion layer and the ions transferred by the hydrogel layer and catalyzes the reaction, and the products after the reaction further diffuse under the concentration gradient.
[0022] Furthermore, the gas diffusion layer is a type of hydrophobic porous medium material, including a macroporous substrate layer and a microporous layer.
[0023] Furthermore, the catalytic layer is arranged in the anode electrode system of the CO2 mineralization battery system.
[0024] Furthermore, the hydrogel layer is used to establish a "water blocking zone" between the electrode liquid and the catalyst layer, which can effectively avoid the problem of electrode flooding caused by the pressure difference of the two-phase flow on both sides of the electrode and the capillary phenomenon; and the properties of the hydrogel layer can be controlled by changing the process parameters of directional freezing and salting-out treatment, thereby broadening the scope of application of the electrode system.
[0025] The beneficial effects of the present invention include:
[0026] (1) The present invention uses temperature gradient as the driving force, and prepares a hydrogel gas diffusion electrode through the synergistic effect of directional freezing and salting-out effect. Microscopic ordered channels are constructed in the hydrogel layer through directional freezing, and the structural stability of the gel layer is further enhanced by salting-out treatment, and the transport rate of ions is increased. The prepared hydrogel layer is flexible and has a certain mechanical strength, and can exist stably in a three-phase environment. And the structure and properties of the hydrogel layer of the electrode system can be regulated by changing the process parameters. The present invention verifies the mass transfer effect of hydrogel layers with different structures on ions and free water, realizes the preparation and regulation of high-performance hydrogel composite electrodes, and can solve the risk of electrode flooding.
[0027] (2) The present invention prepares a directional freezing and salting-out hydrogel gas diffusion electrode. The core innovative idea is to create a hydrogel layer on the electrode surface to achieve ion transport across the gel layer, while forming a water block to achieve "water surge prevention". The electrode preparation method of the present invention utilizes the synergistic effect of directional freezing and salting-out effects to in situ self-grow a layer of conductive hydrogel electrode layer with certain mechanical strength and microscopic order on the surface of the gas diffusion electrode catalyst layer, thereby constructing a three-layer electrode system with a gas diffusion layer-catalytic layer-hydrogel layer. Induce the conversion of free water at the contact interface between the hydrogel layer and the solution into bound water, thereby solving the risk of flooding of the gas diffusion layer, and relying on the microscopic ordered channels of the gel layer to achieve efficient directional diffusion of ions and enhance ion transport.
[0028] (3) The concept of the hydrogel electrode proposed in the present invention is based on the existence of a CO2 mineralization battery system in which the electrode is "flooded", resulting in a loss of electrode life and electrode failure. However, the entire electrode of the present invention is an innovative improvement based on a traditional gas diffusion electrode, and is universal and can be used in a variety of electrochemical systems in which a gas-liquid-solid three-phase reaction exists. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0030] Figure 1a Schematic diagram of the hydrogel electrode system prepared for directional cryo-salting out;
[0031] Figure 1b Schematic diagram of the hydrogel electrode system prepared for directional cryo-salting out;
[0032] Figure 2 is a flow chart of the preparation method of Example 1 of the present invention;
[0033] Figure 3 is a schematic diagram of an oriented porous structure parallel to the diffusion direction formed in the gel layer;
[0034] Figure 4 is a schematic diagram showing that the structure formed in the gel layer is an oriented fibrous structure perpendicular to the diffusion direction;
[0035] Figure 5 It is the ion chromatography test and calculation results;
[0036] Figure 6 To verify the effect of the prepared hydrogel layer in preventing water surge;
[0037] Figure 7 To verify the electrochemical performance of the hydrogel gas diffusion electrode;
[0038] Figure 8 It is the water content data under different swelling time;
[0039] Fig. 9 To characterize the mechanical properties of the hydrogel layer;
[0040] In the figure, 1-gas diffusion layer; 2-catalytic layer; 3-hydrogel layer; 4-reaction gas; 5-electrode liquid. DETAILED DESCRIPTION
[0041] All features disclosed in all embodiments in this specification, or steps in all methods or processes implicitly disclosed, except for mutually exclusive features and / or steps, can be combined and / or expanded or replaced in any manner.
[0042] The present invention proposes an effective strategy to solve the technical problems in the background: constructing a hydrogel layer on the surface of the electrode catalyst layer to form a water blocking zone, which prevents the flow and leakage of free water while ensuring the ion transport required for the electrochemical reaction. Hydrogel is a type of extremely hydrophilic polymer with a three-dimensional network structure formed by physical or chemical cross-linking of gel monomers, which has high water absorption, high water retention, and good structural designability and functional adjustability.
[0043] The high-performance power generation hydrogel electrode with freezing-induced directional ion diffusion proposed in the present invention essentially utilizes the synergistic effect brought about by directional freezing technology and the salting-out effect of polymer solution. Under the induction of directional freezing temperature gradient, the liquid water in the polymer solution is controlled to solidify, and the polymer chains are squeezed out by ice crystals, forming enrichment areas with the ice crystals. During the salting-out process, the ice crystals inside the solid melt, and the solid ice crystals formed by the polymer solution become flexible and elastic hydrogels. Under the action of directional freezing, a directional pore structure is formed inside the gel. Salting-out further enhances the stability of the internal structure of the electrode hydrogel layer and the ion transport performance. The hydrogel electrode and preparation method solve the risk of electrode flooding and realize directional ion transport by self-growing a layer of high-performance hydrogel layer on the surface of the electrode catalyst layer.
[0044] Specifically, first, a layer of polymer precursor solution (such as polyvinyl alcohol) is uniformly coated on the original gas diffusion electrode catalyst layer. Under the induction of freezing temperature gradient, the polymer solution is controlled to solidify, and the polymer chain is squeezed by ice crystal growth to form an oriented micron-scale pore structure. Secondly, the electrode with the gel layer solidified is immersed in a salt solution (such as NaOH) to assist in thawing and is exposed to hydrophilic OH. -The surface tension between the polymer chain and the water molecules changes due to the influence of the gas diffusion electrode system. At this time, there are multiple interactions between the lyophilic ions, polymer chains and water in the system. Under these interactions, the polymer chain structure in the hydrogel is fixed and strengthened. The polymer solution undergoes a three-phase change from liquid to solid to gel. Free water is converted into bound water. The directional freezing induction and salting-out effects build a high-performance ion transport channel inside the gel. Compared with the traditional gas diffusion electrode system, this electrode system can simultaneously achieve free water barrier and efficient ion transport.
[0045] The present invention proposes a high-performance hydrogel gas diffusion electrode capable of achieving directional ion diffusion based on directional freezing temperature gradient induction and a preparation method thereof. Among them, the structure of the entire electrode mainly includes: ① gas diffusion layer; ② catalyst layer; ③ hydrogel layer. The overall structure is similar to the electrode composition in the hydrogen-oxygen fuel cell system. Among them, the gas diffusion layer directly contacts the reaction gas, and the catalyst layer directly contacts the electrode liquid; the catalyst is attached to the catalyst layer to provide reaction sites for the gas adsorbed by the gas diffusion layer and the ions transferred by the hydrogel layer and catalyze the reaction. The three-layer electrode system of gas diffusion layer-catalyst layer-hydrogel layer realizes the transformation of free water to bound water with the help of the hydrogel layer, and at the same time has efficient ion transport performance, which can effectively solve the problem that the traditional gas diffusion electrode is easily flooded by water and causes electrode failure during the gas-liquid-solid three-phase reaction.
[0046] Furthermore, the gas diffusion layer (GDL) is a type of hydrophobic porous medium material, which consists of a macroporous base layer (GDB) and a microporous layer (MPL). It is located between the gas flow field and the catalyst layer, acting as a carrier for water vapor transport, heat transfer, and electron conduction, and provides structural support during assembly and operation. The thickness of the gas diffusion layer is between 100 and 400 μm. The base layer is composed of anisotropic stacked carbon fibers and is in direct contact with the gas; the microporous layer is a mixture of carbon-based powder and a hydrophobic agent, and is in direct contact with the catalyst layer. The performance of the gas diffusion layer material directly affects the progress of the electrochemical reaction and the working efficiency of the battery, and at the same time plays an important bridge role in the entire electrode.
[0047] Furthermore, the catalyst layer is an important component of the electrode system. For the CO2 mineralization battery system, the catalyst layer in the anode electrode system can promote the oxidation reaction of hydrogen, involving multiple processes such as oxidation reaction, gas diffusion, electron movement, proton movement, water migration, etc. A good catalyst layer should have good catalytic activity, high proton conductivity, high electron conductivity, good water management ability, and gas diffusion ability.
[0048] Furthermore, the hydrogel layer is the novelty of the electrode system and the difference between the gas diffusion electrode system and other similar electrode systems in terms of water management. By self-growing the hydrogel layer, a "water blocking zone" is established between the electrode liquid and the catalyst layer, which can effectively avoid the problem of electrode flooding caused by the pressure difference of the two-phase flow on both sides of the electrode and the capillary phenomenon. At the same time, the in-situ hydrogel layer prepared by directional freezing-salting out can ensure the directional diffusion of the reaction ions and close contact with the catalyst layer due to its internal microscopic ordered orientation structure and the inherent characteristics of the high water content of the hydrogel, providing abundant reaction sites for the gas-liquid-solid three-phase reaction. In this electrode system, the properties of the hydrogel layer can also be controlled by changing the process parameters of directional freezing and salting out treatment, further broadening the scope of application of the electrode system; in addition, the hydrogel layer also has excellent softness and elasticity, can adapt to different shapes of surfaces, and maintain the stability and reliability of the electrode. These advantages make this electrode system widely used in systems with gas-liquid-solid three-phase reactions, such as CO2 mineralization batteries, CO2 electrochemical capture systems, and electrochemical-related sensors with gas-liquid-solid three-phase states.
[0049] like Figure 1a and Figure 1b As shown in the figure, it is a schematic diagram of the principle of the hydrogel electrode system prepared by directional freezing and salting out proposed in the present invention. The principle of the hydrogel electrode system of freezing-induced ion directional diffusion is as follows Figure 1b As shown. The gas diffusion layer 1 is in direct contact with the reaction gas 4, and the gas diffuses into the electrode system through the macroporous substrate layer and the microporous layer under the action of the concentration gradient. The hydrogel layer 3 is in direct contact with the electrode liquid 5. The hydrogel layer 3 is a semi-solid gel. The free water in the electrolyte cannot freely diffuse out of the electrode system through the hydrogel layer under pressure and concentration gradient; and the ion channels inside the hydrogel layer 3 can transport the ions in the electrode liquid to the catalyst layer for reaction. The catalyst layer 2 is the place where the electrochemical reaction of the gas diffusion electrode occurs. The catalyst layer 2 adsorbs the reaction gas diffused from the gas diffusion layer and the ions transported by the hydrogel layer; under the action of the catalyst attached to the catalyst layer, the gas reacts with the ions. The products after the reaction further diffuse under the concentration gradient. The electrode system induces the conversion of free water into bound water through the blocking effect of the hydrogel layer, solves the problem of easy "flooding" of the traditional gas diffusion electrode, and realizes the directional transport of ions and the efficient solid-liquid-gas three-phase reaction.
[0050] The solution of the present invention has the following advantages:
[0051] (1) The electrode system of the present invention is different from the traditional gas diffusion electrode water management concept. It forms a free water blocking zone by in-situ self-growing hydrogel layer and inducing the conversion of interfacial free water into bound water, thereby solving the problem of easy flooding of traditional gas diffusion electrode systems.
[0052] (2) The internal ordered microstructure of the hydrogel layer of the electrode system of the present invention can regulate the ion transport performance. By controlling the directional freezing temperature gradient, the internal ice crystal growth direction when the polymer solution solidifies can be changed, thereby changing the microscopic pore structure in the hydrogel layer. That is, the gel layer prepared under different freezing directions has different microstructures. When the ions in the electrode solution diffuse in the hydrogel layers with different structures, there are differences in the mass transfer paths and the diffusion fluxes are different.
[0053] (3) The present invention can change the salting-out environment during the preparation of the hydrogel layer of the system, and can regulate the mechanical strength and ion transport performance of the hydrogel layer. The electrode system after the gel layer is frozen and solidified is immersed in a salt solution for salting-out assisted thawing. Under the influence of different hydrated ions and polymer system environments, there are differences in the interactions between the lyophilic ions, polymer chains and water in the system, and there are also differences in the internal structure and strength of the hydrogel layer. These differences lead to different diffusion fluxes of the hydrogel layer for the same ion.
[0054] (4)) The hydrogel layer of the electrode system of the present invention is flexible and elastic, and can also be applied to flexible electrode systems that require gas-liquid-solid three-phase reactions.
[0055] (5) The electrode of the present invention can be adapted to a variety of application environments by improving the gas diffusion layer, the catalyst layer and the hydrogel layer; the entire electrode system can be designed as a simple small gas diffusion electrode according to needs, or it can be designed into a large-scale integrated system through system design and series-parallel connection.
[0056] (6) The hydrogel layer in the electrode system of the present invention has high water content and hydrophilic properties. Due to the effect of the polymer network inside the hydrogel, the flow of free water in the hydrogel is blocked, which can effectively isolate the passage of free water. However, the ion channels inside the hydrogel can induce ion diffusion.
[0057] (7) The polymer solution system used to construct the hydrogel layer in the electrode system of the present invention is replaceable, and the solutes in the polymer precursor solution include but are not limited to various hydrophilic polymers such as PVA, sodium alginate, and chitosan.
[0058] (8) The solute of the salting-out solution in the electrode system of the present invention is replaceable, and the cation includes but is not limited to Na + , K + NH4 + , Ca 2+ The anions include but are not limited to citrate, SCN - 、ClO4 - ,I - 、NO3 - Br - Anions.
[0059] It should be noted that within the scope of protection defined in the claims of the present invention, the following embodiments can be combined and / or expanded or replaced in any logical way from the above specific implementation methods, such as disclosed technical principles, disclosed technical features or implicitly disclosed technical features.
[0060] In other embodiments, such as the following embodiments, the raw materials and their sources are as follows: analytically pure PVA2099, trisodium citrate, and sodium hydroxide are directly used as experimental raw materials.
[0061] Example 1
[0062] The process of this embodiment is shown in the attached Figure 2 As shown, the system structure is as Figure 1b As shown, this embodiment provides a hydrogel electrode system for cryo-induced ion directional diffusion, which includes a reaction gas 4 and an electrode liquid 5, which are in direct contact with a gas diffusion layer 1 and a hydrogel layer 3 respectively. The gas diffuses into the electrode system through the gas diffusion layer composed of a macroporous substrate and a microporous layer under the action of a concentration gradient. The reaction ions in the electrode liquid diffuse through the ion channels in the hydrogel layer under the action of the concentration gradient, and the reaction ions are transported to the catalyst layer 2, and react with the reaction gas at the reaction sites on the catalyst layer 2.
[0063] The catalyst layer 2 in the system adsorbs the reaction gas 4 diffused from the gas diffusion layer 1 and the ions transported by the hydrogel layer; the gas and the ions undergo an electrochemical reaction under the action of the catalyst attached to the catalyst layer 2. The reaction products further diffuse under the action of the concentration gradient and are transported to the electrode solution through the gel layer.
[0064] In this system, the hydrogel layer 3 is a semi-solid gel, and the free water in the electrode liquid cannot diffuse freely through the hydrogel layer 3 to the catalyst layer under pressure and concentration gradient; the hydrogel layer 3 forms a microscopic pore structure due to directional freezing, and the internal structure and stability of the hydrogel layer are further stabilized under the action of ions during the subsequent salting-out process. At the same time, the hydrogel layer reaches swelling equilibrium and is in an ion-rich state. In summary, the hydrogel layer 3 plays the role of ion transport and water blocking at the same time, which can solve the problem of electrode system failure caused by "water surge" in the gas diffusion electrode, and greatly increase the service life and stability of the electrode system.
[0065] In this embodiment, the effective area of the electrode system can be 4 cm 2 , the catalyst is a platinum-carbon catalyst.
[0066] In the corresponding preparation method, the specific preparation process is as follows: cut a 2 cm square gas diffusion layer as the electrode system substrate, spray the catalyst on the contact surface between the gas diffusion layer and the catalyst layer, and construct the catalyst layer 2. Evenly apply a layer of PVA solution with a mass fraction of 10% on the surface of the catalyst layer 2 to construct the precursor of the hydrogel layer 3. At this time, the entire electrode system is in contact with a copper plate partially immersed in -80°C ethanol. Under the action of the temperature gradient on the surface of the supercooled copper plate, the hydrogel layer 3 quickly solidifies from a liquid state to a solid state. Next, the solidified electrode system is immersed in a sodium hydroxide solution with a mass fraction of 50%. In the sodium hydroxide solution, the hydrogel layer 3 thaws and changes from a solid state to a gel state. At the same time, a salting-out effect occurs in the ionic environment. The polymer chains in the hydrogel layer 3 undergo a certain degree of crystallization behavior, and the structure is stabilized and enhanced to a certain extent. As the thawing and salting-out proceed, the gel layer reaches swelling equilibrium in the sodium hydroxide solution.
[0067] Example 2
[0068] This embodiment is a refinement of embodiment 1, and further introduces how to construct an oriented structure parallel to the diffusion direction in the gel layer 3 and a test method for characterizing the ion mass transfer performance of the prepared hydrogel layer. According to the preparation process of embodiment 1, when the electrode system precursor attached with the gel solution is in contact with the surface of the supercooled copper plate, the direction perpendicular to the plane of the square gel layer is selected as the direction of the freezing temperature gradient. Under the action of this temperature gradient, the water inside the PVA solution grows into ice crystals along this direction. Taking the ion diffusion direction as a reference, the structure finally formed in the gel layer is an oriented porous structure parallel to the diffusion direction, such as Figure 3 When ions in the electrode liquid diffuse through the oriented porous structure, the mass transfer path is short, the mass transfer resistance is small, and the ion diffusion rate is high, which is suitable for gas-liquid-solid electrochemical three-phase reaction systems with high reaction rate requirements.
[0069] The corresponding preparation method includes the following specific test process: the prepared hydrogel layer is fixed between two liquid phase chambers, the left chamber is deionized water at a certain height, and the right chamber is a 0.5 mol / L NaCl solution at the same height. At room temperature and pressure, the Cl in the right chamber - Under the influence of the concentration gradient, it diffuses to the left. After a certain period of diffusion, the solution in the left chamber is taken and its Cl is measured using ion chromatography. - According to the thickness and mass transfer area of the hydrogel layer, the Cl content per unit of the hydrogel layer can be calculated. - Transmittance.
[0070] Example 3
[0071] This example is a refinement of Example 1, and further introduces how to construct an oriented structure perpendicular to the diffusion direction in the gel layer and analyzes the ion mass transfer performance of the hydrogel layer prepared in parallel and perpendicular (relative to the ion diffusion direction) directions. According to the preparation process of Example 1, when the electrode system precursor is in contact with the surface of the supercooled copper plate, the direction parallel to the plane of the square gel layer is selected as the direction of the freezing temperature gradient. Under the action of this temperature gradient, the water inside the PVA solution grows into ice crystals along this direction. Taking the ion diffusion direction as a reference, the structure finally formed in the gel layer is an oriented fibrous structure perpendicular to the diffusion direction, such as Figure 4 When ions in the electrode liquid diffuse through the oriented porous structure, the mass transfer path is long, subject to greater mass transfer resistance, and the ion diffusion rate is low, which is suitable for gas-liquid-solid electrochemical three-phase reaction systems with low reaction rate requirements.
[0072] In the corresponding preparation method, the following hydrogel layer ion mass transfer performance analysis process is included: Figure 5 As shown in the figure, the ion chromatography test and calculation results show that the hydrogel layer prepared under the temperature gradient parallel to the diffusion direction in Example 2 has a higher unit transmittance of 76.48 mg mm cm -2 d -1 ; The hydrogel layer prepared under the temperature gradient perpendicular to the diffusion direction in Example 3 has a lower unit transmittance of 43.76 mg mm cm -2 d -1 , which is 57.2% of the parallel direction test results. Figure 3 Figure 4 SEM images show that the ion mass transfer performance of the hydrogel layer is related to its internal microstructure, and there is a certain structure-activity relationship.
[0073] Example 4
[0074] This example is to verify the effect of preparing the hydrogel layer in Example 1 to prevent water surge. Figure 6 As shown in the figure, the corresponding preparation method also includes the following specific operation process: the catalyst carbon paper and the hydrogel-catalyst carbon paper are cut into appropriate sizes, clamped in the middle of the H-type electrolytic cell, 20 mL of clean water is added to one side of the electrolytic cell, the rubber plug is covered, and the device is left to stand for 12 hours under hydrostatic pressure, and the carbon paper leakage is observed on the other side of the electrolytic cell. The experimental results show that the device holding the catalyst carbon paper has obvious leakage after standing for 12 hours, while the hydrogel-catalyst carbon paper device has no obvious leakage after standing for 12 hours, which proves that the prepared hydrogel gas diffusion electrode has good anti-surge effect.
[0075] Example 5
[0076] This example is to verify the electrochemical performance of the hydrogel gas diffusion electrode in Example 1. Figure 7As shown, in the corresponding preparation method, the following operation process is also included: use an electrochemical workstation to perform unipolar hydrogen evolution tests on carbon paper, catalyst carbon paper, and hydrogel-catalyst carbon paper. The LSV test results show that the overpotential of the unsprayed catalyst carbon paper is higher, and the current is much smaller than that of the catalyst carbon paper and hydrogel-catalyst carbon paper at the same voltage. Compared with the catalyst carbon paper with the best performance, the performance of the hydrogel-catalyst carbon paper is attenuated but not to a large extent, and it still has a lower overpotential and a higher hydrogen evolution current.
[0077] Comparative Example 6
[0078] The preparation process of this comparative example is basically the same as that of Example 1, except that the salting-out liquid is replaced with trisodium citrate solution of different concentrations, and the swelling behavior of the prepared different hydrogel layers in clean water is compared and studied. The specific operation process is: the electrode system precursor prepared by freezing under a vertical temperature gradient is immersed in clean water, and thawed and salted out in 0.5M, 1.0M, 1.5M, and 2.0M trisodium citrate solutions for 1 day to prepare different hydrogel layers. These different hydrogel layers are immersed in clean water respectively, and the change of their mass with the immersion time is tested using a balance. Combined with the dry weight of the gel layer after air-drying, the water content data at different swelling times is calculated. The results are as shown in the figure. Figure 8 As shown, in general, the water content of the hydrogel layer prepared by the method of the present invention shows a swelling process in which the water content first rises and then stabilizes during the swelling process, which is limited swelling and shows stability in an aqueous environment. The hydrogel layer prepared using different trisodium citrate solutions has different swelling characteristics in deionized water: as the concentration of the trisodium citrate solution increases, the time for the hydrogel layer to reach swelling equilibrium gradually shortens, and the water content gradually decreases at the same swelling time. This shows that different concentrations of salting-out liquid treatment will also have different effects on the structure of the hydrogel layer. Therefore, the present invention can achieve a certain degree of regulation on the structure and properties of the hydrogel layer by changing the concentration of the salting-out liquid.
[0079] Example 7
[0080] This example characterizes the mechanical properties of the hydrogel layer prepared in Example 3. The corresponding preparation method also includes the following specific operation process: the prepared hydrogel layer is cut into 5 dog bone-shaped strips of similar size, and a universal material testing machine is used to perform a tensile test to obtain stress-strain data of the hydrogel layer strips, such as Fig. 9 As shown. The results show that the stress-strain curve data of the hydrogel layer are relatively concentrated, indicating that the hydrogel layer has good uniformity. At the same time, the stress range of the five splines is 5.44-7.46MPa, and the elongation at break ranges from 534-684%, indicating that the prepared hydrogel layer has good mechanical properties.
[0081] In summary, the high-performance hydrogel electrode system for freeze-induced directional ion diffusion disclosed in the present invention utilizes the synergistic effect of directional freezing and salting-out effect, and in situ self-grows a hydrogel layer on the surface of the catalyst layer of the traditional gas diffusion electrode, thereby converting the catalyst layer-electrode liquid contact surface of the traditional gas diffusion electrode system into catalyst layer-gel layer-electrode liquid, inducing the catalyst layer contact surface to be converted from free water to bound water, and realizing water blocking and ion transport through the hydrogel layer, thereby realizing the gas diffusion electrode's anti-"water surge" function.
[0082] Secondly, the hydrogel layer prepared by the electrode system of the present invention exhibits good swelling stability in clear water and has high mechanical properties. The properties of the gel layer can be further regulated by changing the direction of the freezing temperature gradient, the salting-out environment and other parameters, and the ion transport performance of the gel layer can be adjusted under the premise of water isolation, so as to adapt to different application environments.
[0083] The above-mentioned examples are only preferred embodiments of the present invention, but the protection scope of the present invention is not limited thereto. It should be pointed out that, for ordinary technicians in this technical field, according to the technical solution and patent concept of the present invention, several improvements and modifications can be made without departing from the principle of this patent, and these improvements and modifications should also be regarded as within the protection scope of the present invention.
Claims
1. A method for preparing a hydrogel electrode for cryo-induced ion directional diffusion, characterized in that: The following steps are involved: Step 1, pre-uniformly coating a polymer precursor solution on the catalyst layer, setting a freezing temperature gradient induction, so that the polymer solution is controlled to solidify, and during the solidification process, the polymer chain is squeezed by the growth of ice crystals to form an oriented micron-scale pore structure; Step 2, immersing the electrode after the hydrogel layer is solidified in a salt solution to assist thawing. Under the influence of the hydrophilic group, the surface tension between the polymer chain and the water molecules changes. At this time, there are multiple interactions between the lyophilic ions, polymer chains and water in the system. These interactions are used to fix and enhance the polymer chain structure in the hydrogel. The polymer solution undergoes a liquid-solid-gel three-phase change, free water is converted into bound water, and directional freezing induction and salting-out effects construct ion transport channels inside the gel.
2. The method for preparing a hydrogel electrode for freeze-induced ion directional diffusion according to claim 1, characterized in that: The freezing temperature gradient induction is set to control the solidification of the polymer solution. During the solidification process, the polymer chains are squeezed by the growth of ice crystals to form an oriented micron-scale pore structure. The method specifically includes the following sub-steps: Construct an oriented structure parallel to the diffusion direction in the gel layer: select the direction perpendicular to the plane of the square gel layer as the direction of the freezing temperature gradient. Under the action of this temperature gradient, the water inside the precursor solution grows into ice crystals along this direction. Taking the ion diffusion direction as a reference, the structure finally formed in the gel layer is an oriented porous structure parallel to the diffusion direction.
3. The method for preparing a hydrogel electrode for cryo-induced ion directional diffusion according to claim 1, characterized in that: The freezing temperature gradient induction is set to control the solidification of the polymer solution. During the solidification process, the polymer chains are squeezed by the growth of ice crystals to form an oriented micron-scale pore structure. The method specifically includes the following sub-steps: Construct an oriented structure perpendicular to the diffusion direction in the gel layer: select the direction parallel to the plane of the square gel layer as the direction of the freezing temperature gradient. Under the action of this temperature gradient, the water inside the precursor solution grows into ice crystals along this direction. Taking the ion diffusion direction as a reference, the structure finally formed in the gel layer is an oriented fibrous structure perpendicular to the diffusion direction.
4. The method for preparing a hydrogel electrode for freeze-induced ion directional diffusion according to claim 1, characterized in that: The precursor solution includes any one of polyvinyl alcohol (PVA) solution, chitosan, sodium alginate and gelatin.
5. The method for preparing a hydrogel electrode for freeze-induced ion directional diffusion according to claim 1, characterized in that: The freezing temperature gradient induction setting includes any one of uniform random freezing, parallel orientation freezing, and vertical orientation freezing.
6. The method for preparing a hydrogel electrode for freeze-induced ion directional diffusion according to claim 1, characterized in that: The cations in the salt solution include Na + , K + NH4 + , Ca 2+ Any one of; anion citrate, SCN in the salt solution - 、ClO4 - ,I - 、NO3 - Br - Any of the ions.
7. A hydrogel electrode system for cryo-induced ion directional diffusion, characterized in that: include: Gas diffusion layer, catalyst layer and hydrogel layer; The gas diffusion layer is in direct contact with the reaction gas, and the gas diffuses into the electrode system through the macroporous base layer and the microporous layer under the action of the concentration gradient; the hydrogel layer is a semi-solid gel and is in direct contact with the electrode liquid. The free water in the electrolyte cannot freely diffuse out of the electrode system through the hydrogel layer under pressure and concentration gradient. There are ion channels inside the hydrogel layer, and the ions in the electrode liquid are transported to the catalytic layer for reaction, thereby utilizing the hydrogel layer to realize the conversion of free water into bound water; the catalytic layer adsorbs the reaction gas diffused from the gas diffusion layer and the ions transported by the hydrogel layer, and is in direct contact with the electrode liquid; the catalytic layer is attached with a catalyst, which provides reaction sites for the gas adsorbed by the gas diffusion layer and the ions transferred by the hydrogel layer and catalyzes the reaction, and the products after the reaction further diffuse under the concentration gradient.
8. The hydrogel electrode system for cryo-induced ion directional diffusion according to claim 7, characterized in that: The gas diffusion layer is a type of hydrophobic porous medium material, including a macroporous base layer and a microporous layer.
9. The hydrogel electrode system for cryo-induced ion directional diffusion according to claim 7, characterized in that: The catalyst layer is arranged in the anode electrode system of the CO2 mineralization battery system.
10. The hydrogel electrode system for cryo-induced ion directional diffusion according to claim 7, characterized in that: The hydrogel layer is used to establish a "water blocking zone" between the electrode liquid and the catalyst layer, which can effectively avoid the problem of electrode flooding caused by the pressure difference of the two-phase flow on both sides of the electrode and the capillary phenomenon; and the properties of the hydrogel layer can be controlled by changing the process parameters of directional freezing and salting-out treatment, thereby broadening the scope of application of the electrode system.
Citation Information
Patent Citations
Application of carbon aerogel in membrane electrode of miniature direct methanol fuel cell as cathode water absorption layer
CN109713319A
Janus double-layer aerogel as well as preparation method and application thereof
CN115725112A
Preparation method of hydrogel with highly-oriented microstructure
CN116178750A
Lithium battery pole piece and preparation method thereof
CN117594750A
Porous gas diffusion electrode for fuel battery and preparing method thereof
CN1553534A
